On the openness and discreteness of mappings with unbounded characteristic of quasiconformality - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The paper is devoted to the investigation of the topological properties of space mappings. It is shown that sense-preserving mappings f : D → R^n in a domain D R^n, n ≥ 2, which are more general than mappings with bounded distortion, are open and discrete if a function Q corresponding to the control of the distortion of families of curves under these mappings has slow growth in the domain f(D), e.g., if Q has finite mean oscillation at an arbitrary point y0 f(D).